MENUMBUHKAN KESEJAHTERAAN BERSAMA DESA PANGARENGAN MELALUI PENDIDIKAN, KESEHATAN, DAN PEMBERDAYAAN MASYARAKAT - Abdullah Gymnastiar; Nangroe Kana Nirmala; Farhan Fauzi Zuhair; Ananda Rangga Zaki Ramadhan; Fitria Salsabila Salma; Muhammad Fadhil Putra; Gilang Bayu Saputra; Ila Dayana; Muhamad Bagas Riyanto; Hanni Azhari; Eza Fatiha Zahra; Dzaky Faqihul Izza; Elfriza Putri Indrayanti; Sayidati Shabrina Seno (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Pangarengan Village has various potentials that can be developed, but still faces challenges in terms of strengthening village identity. One of the main problems faced is the weak branding of village identity, which has an impact on the low attractiveness and recognition of the village in the eyes of the public. This Thematic Student Work Lecture (KKM) of Sultan Ageng Tirtayasa University aims to strengthen the identity of Pangarengan Village through the “Branding Identity” program and develop community awareness in health, education, and economic aspects. The method used in this activity is a participatory-based partnership by involving the community in various programs such as branding identity, anti-bullying counseling, financial planning, planting plant seeds, children's education activities, immunization, joint sports, non-communicable disease counseling, and Indonesian Independence Day celebrations. The results of these activities show positive changes in the mindset and behavior of the community, especially in awareness of healthy living and the importance of financial planning. The community began to exercise regularly and MSME players showed commitment in saving habits.Keywords: Village Branding; Community Empowerment; Health and Financial Awareness.